2017
DOI: 10.1002/2017wr020570
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Investigation on Biofilm Distribution and Its Impact on Macroscopic Biogeochemical Reaction Rates

Abstract: Biofilms are critical locations for biogeochemical reactions in the subsurface environment. The occurrence and distribution of biofilms at microscale as well as their impacts on macroscopic biogeochemical reaction rates are still poorly understood. This paper investigated the formation and distributions of biofilms in heterogeneous sediments using multiscale models and evaluated the effects of biofilm heterogeneity on local and macroscopic biogeochemical reaction rates. Sediment pore structures derived from X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…While the role of a catchment as a hydrologic filter has been relatively well explored in different contexts (Dwivedi et al, 2020; Guan et al, 2011), and it has been widely accepted that the properties of filtering in a catchment could be linked more explicitly to the underlying mechanistic processes of rainfall‐runoff response (Kirchner, 2009), few studies have investigated the potentials of such a perspective in characterizing subsurface processes (e.g., PF) leading to runoff (Labat et al, 2005). PF‐dominated soil structure is often considered a dual‐pore network: a “primary” network of large (macro) pores overlapped by a “secondary” network of small (micro) pores (Frey et al, 2012; Kodesova et al, 2010; Tsakiroglou & Ioannidis, 2008; Yan et al, 2017). Accordingly, a soil system is supposed to provide dual‐pore filtering, through which the smoothing effects are likely to be stronger for matrix flows and weaker for PF via macropores (Guan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While the role of a catchment as a hydrologic filter has been relatively well explored in different contexts (Dwivedi et al, 2020; Guan et al, 2011), and it has been widely accepted that the properties of filtering in a catchment could be linked more explicitly to the underlying mechanistic processes of rainfall‐runoff response (Kirchner, 2009), few studies have investigated the potentials of such a perspective in characterizing subsurface processes (e.g., PF) leading to runoff (Labat et al, 2005). PF‐dominated soil structure is often considered a dual‐pore network: a “primary” network of large (macro) pores overlapped by a “secondary” network of small (micro) pores (Frey et al, 2012; Kodesova et al, 2010; Tsakiroglou & Ioannidis, 2008; Yan et al, 2017). Accordingly, a soil system is supposed to provide dual‐pore filtering, through which the smoothing effects are likely to be stronger for matrix flows and weaker for PF via macropores (Guan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling results for a heterogenous aquifer system has also suggested that zones of higher conductivity result in hotspots of chemical reactivity due to enhanced mixing (Pool and Dentz, 2018). Microscale modeling work has again suggested that biofilm distribution and biogeochemical activity are increased along preferential flow paths (Yan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In the two experiments with moist soils, we documented a CH 4 loss of of ~0.09 ppmv h -1 within the common window of CH 4 concentration decline ( Fig 3A ), as determined by subtracting the diffusive CH 4 loss in blank experiments from the bulk CH 4 loss in experiments #10 and #11 with soils ( Table 1 ). It is well established that heterogeneously distributed methanotrophic biofilms in the subsurface [ 28 ] are capable of scavenging CH 4 from the atmosphere (e.g., [ 29 , 30 ]). Soil gas can often reach 222 Rn radiation levels of many thousand Bq m -3 , depending on local geology [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%